1991
DOI: 10.1016/0378-1097(91)90555-o
|View full text |Cite
|
Sign up to set email alerts
|

Expression in Caulobacter crescentus of the phosphate-starvation-inducible porin OprP of Pseudomonas aeruginosa

Abstract: The gene for the phosphate-starvation-inducible outer membrane protein OprP, of Pseudomonas aeruginosa was introduced into Caulobacter crescentus CB2A on a plasmid vector. As is the case in P. aeruginosa and Escherichia coli the oprP gene was inducible under conditions of limiting phosphate in C. crescentus. However, the maximal medium concentration of phosphate which still permitted induction of OprP was lower in C. crescentus (50 microM) than in P. aeruginosa (200 microM). Induction of OprP was coincident wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Efficient stalk elongation, even under conditions of phosphate limitation, still appears to be dependent on rpoN gene expression. It has been shown that the expression of a Pseudomonas aeruginosa phosphate starvation-inducible porin is increased in C. crescentus in response to phosphate limitation (Walker et al 1991). Because the gene encoding this phosphate starvation-inducible porin contains the promoter regulatory sequences enabling it to be regulated by the phosphate regulon in P. aeruginosa, these results suggest that C. crescentus also possesses a similar phosphate regulon.…”
Section: O ~4 Is Required For Cell Cycle-dependent Stalk Biosynthesismentioning
confidence: 55%
“…Efficient stalk elongation, even under conditions of phosphate limitation, still appears to be dependent on rpoN gene expression. It has been shown that the expression of a Pseudomonas aeruginosa phosphate starvation-inducible porin is increased in C. crescentus in response to phosphate limitation (Walker et al 1991). Because the gene encoding this phosphate starvation-inducible porin contains the promoter regulatory sequences enabling it to be regulated by the phosphate regulon in P. aeruginosa, these results suggest that C. crescentus also possesses a similar phosphate regulon.…”
Section: O ~4 Is Required For Cell Cycle-dependent Stalk Biosynthesismentioning
confidence: 55%
“…Thus, PhoB could act directly by binding to the promoters of stalk genes and by stimulating their transcription, or it could indirectly regulate those genes by regulating other regulatory genes. The presence of a PhoB-controlled Pho regulon in Caulobacter was initially suggested by experiments which showed that the expression of oprP from P. aeruginosa, a phosphate-regulated gene whose promoter contains a Pho box, was induced by phosphate starvation in Caulobacter (48). Examination of the promoter regions of the Caulobacter pst genes suggests that Caulobacter PhoB also exerts its regulatory effect by binding to Pho boxes.…”
Section: Discussionmentioning
confidence: 99%